THE CHARACTERISTICS OF STRESS TOLERANCE OF MARRIED AND UNMARRIED PEOPLE, DEPENDING ON THEIR ATTITUDE TO LONELINESS - Psiadlo, Edyard; Shragina, Larysa; Vishtalenko, Olena; Lukashin, Vitaliy (PSYCHOLOGICAL JOURNAL, 2019)
The article discusses the problem of an individual’s psychological hardiness, stress tolerance, loneliness, coping strategies used by people to overcome difficult life situations; the characteristics of stress tolerance of married and unmarried people having a positive / negative attitude to loneliness are identified and compared. The overcoming behaviour was estimated with the projective method “A person in the rain”. Our study show the significantly higher indicator of “shared experience of loneliness” at unmarried people in comparison with that of married people (ρ≤0,002), as well as the higher indicator of “dependence on communication” (ρ≤0,05). As for psychological hardiness and a negative attitude to loneliness, “overall psychological hardiness” of married people is significantly higher compared to that of unmarried people (ρ≤0,002), mainly due to “challenge” indicator (ρ≤0,002). As for psychological hardiness and a positive attitude to loneliness, “overall psychological hardiness” of married people is significantly higher compared to that of unmarried people (ρ≤0.05). The greatest psychological hardiness is shown by married people with a positive attitude to loneliness, the lowest hardiness is shown by unmarried people and who perceive loneliness in a negative aspect. The study of stress tolerance of married and unmarried people shows that married people prefer to use coping strategies such as “planning of problem solving”, “seeking for social support” and “confrontational coping”, while unmarried people prefer to use copying strategies such as “distancing”, “escape-avoidance” and “self-control”. To obtain valid data about the unconscious level, we have developed a system of overcoming behaviour assessment based on the projective method “A person in the rain”. The correlation analysis between the scales of the standardized “Way of Coping Questionnaire” and the scales of the “A person in the rain” projective methodology showed that the proposed by us standardization of the projective method is valid for four scales: “confrontive coping”, “escape-avoidance”, “seeking social support” and “positive reappraisal”. The data on correlations for other four scales indicate necessity to make changes to selection from made drawings of the components determining the correspondence to certain coping strategies.